P31 Effect of glycogen content on ketone body oxidation and glycolysis in the isolated rat heart. (21st March 2018) - Kadir, Azrul Abdul; Chong, Cher-Rin; Lee, Henry; Stubbs, Brianna; Cox, Pete; Clarke, Kieran; Evans, Rhys
Abstract : Apart from acting as an alternative energy source in oxidative tissues, including muscle, ketone bodies regulate the metabolism of other substrates, but are cataplerotic. Glycogen can be mobilised for anaplerosis, regenerating Krebs cycle intermediates, thus glycogen availability may affect the hearts' ability to oxidise ketone bodies. We hypothesise that glycogen acts as an anaplerotic substrate for myocardial ketone body oxidation, and thereby affects cardiac exogenous glucose utilisation. We aimed to determine the effects of cardiac glycogen content and ketone body metabolism on glucose utilisation. Methods: Isolated rat hearts were pre-perfused with buffer containing either no substrate (to deplete glycogen) or pyruvate, lactate, glucose and insulin (to augment glycogen content), before switching to 14C–hydroxybutyrate (βHB) or 5–3 hour-glucose, plus 11 mM glucose. Timed buffer samples were analysed for 14CO2 or 3H2 O to measure βHB oxidation or glycolysis, respectively. Hearts were freeze-clamped for glycogen content. Results: Removal of substrate in the perfusion period significantly decreased myocardial glycogen content (5.4±1.6 vs 43.5±5.1 μmol glycosyl units/gww). βHB oxidation rate in high glycogen hearts was twice that of low glycogen hearts. Presence of βHB in both high and low glycogen hearts significantly decreased glycolysis from perfusate glucose by 60% and 38% respectively (both to 0.29 µmol/gww/min). Conclusion: βHB oxidation was increased, and glycolysis from exogenous glucose was decreased, in high glycogen hearts.